Agro-Morphological Variation Among an Ancient World Barley Collection - Alptekin Karagöz (Journal of Agricultural Sciences)
Historically barley has been a very important crop in agriculture system of Turkey as it is now. Barley breeding and collecting activities started at the beginning of 20th century in Turkey. During that time huge amount of material piled up at the seed banks and collections of plant breeding institutions through collecting missions and material exchange. We characterized around 3.500 barley accessions of Eskisehir Transition Zone Agricultural Research Institute. Characterized populations have been obtained from 44 countries (Asia 14, Europe 19, Americas 6, Africa 4 and Australia) of 5 continents and two international agricultural research institutes since 1950’s up to date. We are presenting only the result of 2.517 two row barley accessions with this paper. Results of the study reveal a series of phenotypic similarities and differences between the materials of several countries. Results also show the existence of a significant amount ofdiversity between the populations which can be used as a source for breeding programs.